Intersecting Traditions and Modernity: Perceptions of Quality Assurance in Outcome-Based Education among Vietnamese University Lecturers - Thuy, Tran Thi; Thuy, Pham Trut; Thao, Le Thanh (Innovare Journal of Education, 2023)
In the continuously evolving landscape of global education, the role of Quality Assurance (QA) in fortifying and maintaining the relevance of teaching and learning processes has grown ever more critical. In this context, Vietnam—a country delicately balancing its rich traditions with a strong push towards modern educational paradigms—offers a unique vantage point. The primary aim of this study was to delve deep into Vietnamese university lecturers’ perceptions regarding the intersection of QA and Outcome-Based Education (OBE), particularly focusing on its ramifications on their academic practices. Adopting a qualitative methodology, we engaged with ten lecturers from two distinct universities in the Mekong Delta. Through semi-structured interviews, participants shared their narratives, which were subsequently analyzed using a thematic analysis approach. This analysis was enriched and contextualized through the lens of established theoretical frameworks. The emergent themes painted a multifaceted picture. While recognizing the transformative potential that QA can bring within the OBE framework, lecturers often found themselves grappling with the challenges of seamlessly integrating traditional teaching methodologies with the demands of OBE. Adding to this complexity were concerns about the potential erosion of the ‘human touch’ in teaching as technological interventions become more pervasive in QA processes. Another intriguing dimension was the interplay of deeply rooted Vietnamese cultural norms with contemporary QA practices, serving at times as barriers while at others as catalysts for innovation. The revelations from this study underscore the imperative for establishing culturally resonant QA systems, crafting comprehensive and contextual training modules, and ensuring a judicious blend of technology and traditional pedagogical practices. While resonating with universal themes in education, the findings also spotlight the nuances specific to Vietnam’s academic landscape, making a case for contextually tailored educational interventions.